Smart School Branding: Leveraging AI-Driven Digital Marketing to Enhance Institutional Reputation and Student Enrollment - Annisa Tri Ananda Dewi; Mohamad Ahyar Ma’arif; Muthi’ah Rahman; Moh. Mohlas; Ahmad Rausyan Fikri; Maulidatul Adzimah; Moh Aziz Alwahedi; Moh. Jasri (Journal of Educational Management Research, 2025)
This study aims to examine how AI-driven digital marketing contributes to smart school branding, particularly in enhancing institutional reputation and student enrollment in a selected senior high school context. The research employs a qualitative case study approach to explore the implementation process, stakeholder experiences, and outcomes of integrating artificial intelligence into digital marketing practices. Data were collected through in-depth interviews, non-participant observation, and documentation analysis, and analyzed using data condensation, data reduction, data display, and conclusion drawing techniques. The findings indicate that AI-driven digital marketing improves branding effectiveness through optimized content management, enhanced communication efficiency, and better engagement with prospective students. The integration of AI tools such as analytics systems and chatbots supports faster information delivery and more structured promotional strategies, resulting in increased digital visibility and higher enrollment interest. However, the study also shows that human oversight remains essential to ensure alignment with institutional values and communication quality. The implications suggest that AI serves as a strategic enabler in educational branding, offering both theoretical enrichment for digital marketing studies and practical guidance for schools in adopting technology-driven branding systems.